TRITICALE IN COW FEEDING - A. P. Gaganov; V. N. Zolotarev; Z. N. Zverkova (Зерновое хозяйство России, 2018)
The share of concentrated forage is constantly increasing in the forage balance of the country. The main kind of grain used in husbandry feeding is wheat and it places high demands on soil fertility. Thus the use of such grain crop as triticale is of great importance. It produces stable yields that surpass wheat yields on 25-45% under similar growing conditions. The prime cost of triticale production is on 1.4-1.7% less in comparison with the initial parent forms and barley. Triticale being a hybrid of rye and wheat, inherited not only positive but also negative traits (presence of anti-nutritious substances) that hinders its use in animal feeding. The article gives the results of the study of triticale use instead of barley in the feeding of lactating (dairy) cows. The experiments have been carried out on black-motley cows chosen as similar pairs and divided into two groups with 12 of them each. The animals of the control group received barley bran and the animals of the experimental group received bran of winter triticale of the variety 'Doktrina 110' in the amount of5.5 kgper head a day. There were no other differences in the rations of the animal feeding. The amount of raw protein in the experimental group was higher than that in the control group. It depended on its larger content in triticale (14.5%) than in wheat (11.1%). The replacement of barley on triticale in the ration of lactating cows did not affect greatly on digestion of dry matter, raw oil, but promoted the increase of digestion of raw protein on 5.5%, raw fiber on 1.8% and organic substance on 1.2%. The balance of nitrogen in the control group was negative and in the experimental group it was positive. The replacement of barley on triticale in the ration of lactating cows promoted the increase of average daily milk of natural fat on 7.5% and the decrease of use of dry matter, exchangeable energy and concentrated forage per one kg of milk.